ECONOMIC DEVELOPMENT IN THE VISEGRAD COUNTRIES FROM THE PERSPECTIVE OF MACROECONOMIC IMBALANCE PROCEDURE - Daniel Stavárek (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2015)
The seriousness of problems stemming from macroeconomic imbalances in the EU and particularly in the euro area contributed to introduction of the Macroeconomic Imbalances Procedure which also includes a scoreboard of 11 indicators. The results of the scoreboard serve as an alert mechanism and are interpreted from an economic perspective with a view to identifying developments in the member states that may point to a risk of imbalances. The aim of the paper is to evaluate the risk of imbalances in the Visegrad countries using selected indicators from the scoreboard. Furthermore, the author extends the existing scoreboard methodology of absolute indicators by implementation of relative indices that are more valuable for effectiveness of the policy making process. The results suggest that the only Visegrad country with a significant risk of imbalances is Hungary. However, the relative indicators revealed a sign of possible imbalances also in the Czech Republic and Poland.